ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MOTIVASI EARNINGS MANAGEMENT PADA PERUSAHAAN LQ-45 YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) TAHUN 2009-2013 - WULAN LARASATI, RATU (Jurnal Akuntansi AKUNESA, 2015)
ABSTRACT This research studies factors influencing the practices of earnings management in LQ-45 firms listed on the Indonesian Stock Exchange during 2009-2013. Discretionary accruals that calculated with Jones Modified models (1995) is used to measure the earnings management. Two factors are used in this research are leverage and firm size. Leverage is measured by debt to total assets ratio whereas firm size is measured by natural logarithm (ln) total assets. Research population includes all firms that included in LQ-45 index listed on the Indonesian Stock Exchange continued during the period of February 2009 – July 2009 until August 2013 – January 2014. Sample consists of 85 firms. Data are analysed using multiple linear regressions with results that leverage have negative significant impact on earnings management whereas firm size does not affect earnings management. Keywords : leverage, firm size, discretionary accruals, earnings management